Review of Julia P. Cohen’s Becoming Ottomans: Sephardi Jews and Imperial Citizenship in the Modern Era - Stephanov, Darin (Historein, 2015)
Julia P. Cohen, Becoming Ottomans: Sephardi Jews and Imperial Citizenship in the Modern Era. Oxford: Oxford University Press, 2014. xxi + 219 pp